Efficient evaluation of a gene containment system for poplar through early flowering induction - Briones, María Valentina (2020)
Vertical gene transfer through pollen fow from transgenic or non-native plant species into their crossable natural relatives is a major concern. Gene containment approaches have been proposed to reduce or even avoid gene fow among tree species. However, evaluation of genetic containment strategies for trees is very difcult due to the long-generation times. Early fowering induction would allow faster evaluation of genetic containment in this case. Although no reliable methods were available for the induction of fertile fowers in poplar, recently, a new early fowering approach was developed. In this study, early fowering poplar lines containing the gene construct PsEND1::barnase–barstar were obtained. The PsEND1 promoter was chosen due to its early expression pattern, its versality and efciency for generation of male-sterile plants fused to the barnase gene. RT-PCRs confrmed barnase gene activity in fowers, and pollen development was disturbed, leading to sterile fowers. The system developed in this study represents a valuable tool for gene containment studies in forest tree species.